Synchronous machine operating characteristic and parameter variations / Muhamad Syaiful Mohd Khairudin - Mohd Khairudin, Muhamad Syaiful (2007)
This package presents computer models of electric machines based on the space vector formulation leading to the assessment of the dynamic performance of open and closed-loop AC and DC drive systems. The Simulink / MATLAB implementation is adopted because of its inherent integration of vectorized system representations in block diagram form, of numerical analysis methods, of graphical portrayal of time evolutions of signals combined with the simple realization of the functionality of controllers and power electronic excitations. The development of Simulink models of drive assemblies is a relatively simple task consisting of combining input-output block representation "of the various components making up the system; these blocks can readily be reused (utilizing standard copy and-paste techniques) to modify the system components or the configuration of the system. This approach provides a powerful design tool because of the ease of observing the effects of parameters modifications and of differing system configurations and control strategies.